1995
DOI: 10.1002/cne.903610209
|View full text |Cite
|
Sign up to set email alerts
|

The guidance molecule Semaphorin III is expressed in regions of spinal cord and periphery avoided by growing sensory axons

Abstract: The protein collapsin was purified from chick brain on the basis of its ability to inhibit sensory neuron growth cones, implicating this molecule in sensory axon guidance (Luo et al. [1993] Cell 75:217-227). To examine the relationship between collapsin and sensory axon growth, we examined the pattern of mRNA expression of collapsin's mammalian paralogue, Semaphorin III (Sema III), and compared it to dorsal root ganglion (DRG) axon pathways in the developing rat embryo. Centrally, DRG axons enter the spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 35 publications
4
119
0
2
Order By: Relevance
“…Expression studies of Semaphorin III in rat and chicken revealed a developmentally dynamic expression pattern particularly in the nervous system, the heart, and at the borders of developing bones [Wright et al, 1995;Shepherd et al, 1996]. Correct expression pattern of Sema3a is essential for exact innervations of the neurons during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Expression studies of Semaphorin III in rat and chicken revealed a developmentally dynamic expression pattern particularly in the nervous system, the heart, and at the borders of developing bones [Wright et al, 1995;Shepherd et al, 1996]. Correct expression pattern of Sema3a is essential for exact innervations of the neurons during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, Sema3A is highly expressed and its expression has been shown to correlate with the growth of DRG axons toward their peripheral and central targets (Wright et al, 1995;Giger et al, 1996). Neurons prepared from DRG at this stage die when treated with Sema3A, but death is blocked by high levels of NGF (Ben-Zvi et al, 2006).…”
Section: Semaphorin/plexina3 Signaling Effects On Drg Neuronal Cell Dmentioning
confidence: 99%
“…Sema3A is expressed in ventral spinal cord and acts in vitro as a chemorepellent that is selective for TrkA + axons (Behar et al, 1996;Messersmith et al, 1995;Wright et al, 1995). Correspondingly, studies in mice show that loss-of-function of Sema3A or of its co-receptor neuropilin 1 (Nrp1) results in abnormal penetration of TrkA + sensory axons into the ventral spinal cord (Behar et al, 1996;Gu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%